Combination therapy with vedolizumab and etanercept in a patient with pouchitis and spondylarthritis. Issue 1 (1st February 2017) - Bethge, Johannes; Meffert, Silvia; Ellrichmann, Mark; Conrad, Claudio; Nikolaus, Susanna; Schreiber, Stefan
Abstract : Inflammatory bowel disease is frequently associated with spondylarthritis (SpA). It has been discussed that α4/β7 expressing lymphocytes are involved in the aetiology of SpA. We report a case of a successful combination therapy of vedolizumab (VDZ) and etanercept (ETA) in a patient with ulcerative colitis with pouchitis and SpA. In our case VDZ was effective for pouchitis and ineffective for SpA. The combination with ETA might be a useful treatment strategy to control both diseases and first indications suggest that it is safe. α4/β7 Expressing lymphocytes are most likely not associated in the aetiology of SpA.